2015
DOI: 10.1039/c4cp05943c
|View full text |Cite
|
Sign up to set email alerts
|

Li+ solvation in glyme–Li salt solvate ionic liquids

Abstract: Certain molten complexes of Li salts and solvents can be regarded as ionic liquids. In this study, the local structure of Li(+) ions in equimolar mixtures ([Li(glyme)]X) of glymes (G3: triglyme and G4: tetraglyme) and Li salts (LiX: lithium bis(trifluoromethanesulfonyl)amide (Li[TFSA]), lithium bis(pentafluoroethanesulfonyl)amide (Li[BETI]), lithium trifluoromethanesulfonate (Li[OTf]), LiBF4, LiClO4, LiNO3, and lithium trifluoroacetate (Li[TFA])) was investigated to discriminate between solvate ionic liquids a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

24
305
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 228 publications
(330 citation statements)
references
References 41 publications
(62 reference statements)
24
305
1
Order By: Relevance
“…8(a)]. 99 This stabilization has also been validated by PGSE-NMR measurements of these mixtures, as shown in Fig. 8(b).…”
Section: © -Conducting Ils and Solvate Ilsmentioning
confidence: 66%
See 4 more Smart Citations
“…8(a)]. 99 This stabilization has also been validated by PGSE-NMR measurements of these mixtures, as shown in Fig. 8(b).…”
Section: © -Conducting Ils and Solvate Ilsmentioning
confidence: 66%
“…[89][90][91][92] We explored a variety of such combinations and found that, in certain combinations, these materials have similar properties to conventional aprotic ILs. [93][94][95][96][97][98][99][100][101][102][103][104][105][106][107][108][109] We conclude that these mixtures can be categorized as "solvate ILs," i.e., liquids consisting of a salt and a solvent that strongly coordinates with cations or anions to form stable solvate ions. 110 Detailed studies of the solvate IL on the transport properties, [93][94][95][96][97][98][99] spectroscopic, [99][100][101][102][103] crystallographic, [100][101][102][103] electrochemical, [94][95][96]104,105 quantum mechanical characterizations, [106][107][108]…”
Section: © -Conducting Ils and Solvate Ilsmentioning
confidence: 99%
See 3 more Smart Citations